The influence of technical skills on decision making of novice volleyball players - Mariana Calábria Lopes; Raiane Teixeira Magalhães; Laura Beatriz Faleiro Diniz; João Paulo Abreu Moreira; Maicon Rodrigues Albuquerque (Universidade Federal de Santa Catarina, 2016)
The aim of this study was to verify the influence of the technical skills level on the decision making of novice volleyball players on service, reception and set actions. The sample was composed of 80 novice athletes of school volleyball teams of both sexes. Based on the results from the Volleyball Skills Test Battery, the sample was divided into three groups: low, intermediate and high technical level, by means of One-Way ANOVA. The intermediate group was excluded from further analyses. Decision making was assessed with the Game Performance Assessment Instrument (GPAI). For data analysis purposes, the independent student-t test was used, adopting significance level of p≤0.05. The results showed that players with low skill level in service and set actions also had lower performance on the decision-making test when compared to players with high technical level. On the other hand, in the reception action, no differences were found among groups. It was therefore concluded that the technical level seems to influence the decision making in service and set actions in novice volleyball players.